2022
DOI: 10.3390/s22134864
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Aflatoxin B1 in Single Peanut Kernels by Combining Hyperspectral and Microscopic Imaging Technologies

Abstract: To study the dynamic changes of nutrient consumption and aflatoxin B1 (AFB1) accumulation in peanut kernels with fungal colonization, macro hyperspectral imaging technology combined with microscopic imaging was investigated. First, regression models to predict AFB1 contents from hyperspectral data ranging from 1000 to 2500 nm were developed and the results were compared before and after data normalization with Box-Cox transformation. The results indicated that the second-order derivative with a support vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…and A. flavus enhanced the brightness of the seeds (Figure 2C). This behavior contributed to the increase in reflectance (Fonseca de Oliveira et al, 2022); ii) the formation of mycelia and toxicogenic compounds alters the chemical composition of infected seeds (Zhang et al, 2022), which can reduce light absorption and favor reflection enhancement in the spectral range (Figure 3C); iii) fungal colonization intensifies the production of anthocyanins as a plant response to tissue deterioration (Liu et al, 2018;Fonseca de Oliveira et al, 2022). This pigment, is also produced by fungi (Bu et al, 2020;Sicilia et al, 2021) and its accumulation in the contaminated seeds (Figure 6) may have contributed to the lower reflectance found (Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and A. flavus enhanced the brightness of the seeds (Figure 2C). This behavior contributed to the increase in reflectance (Fonseca de Oliveira et al, 2022); ii) the formation of mycelia and toxicogenic compounds alters the chemical composition of infected seeds (Zhang et al, 2022), which can reduce light absorption and favor reflection enhancement in the spectral range (Figure 3C); iii) fungal colonization intensifies the production of anthocyanins as a plant response to tissue deterioration (Liu et al, 2018;Fonseca de Oliveira et al, 2022). This pigment, is also produced by fungi (Bu et al, 2020;Sicilia et al, 2021) and its accumulation in the contaminated seeds (Figure 6) may have contributed to the lower reflectance found (Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to assess multi-angle organic realities in the electromagnetic spectrum brings promising exploratory power for fungal detection (Boelt et al, 2018). The main reason for this is that the mycelia resulting from fungal colonization changes the surface and chemical composition of the seeds (Zhang et al, 2022). This event generates easily perceptible changes in the spectral range (Franca-Silva et al, 2020;Rego et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the more recent developments in the detection of aflatoxin contamination is the use of spectral technology, including the use of fiber-optic spectrometry [ 14 ], fluorescence hyperspectral imaging [ 15 ], multispectral imaging [ 11 , 16 ], fluorescence spectroscopy [ 17 ], fluorescence spectroscopy and multispectral imaging [ 18 ], ultraviolet–visible–near-infrared spectra [ 19 ], and hyperspectral and microscopic imaging [ 20 ]. A fluorescence hyperspectral study [ 15 ] found that there exists a fluorescence shift toward longer wavelengths in the blue-green spectral region in fungal-infected maize kernels with high aflatoxin content.…”
Section: Introductionmentioning
confidence: 99%